Comparative Study Between Malaysia and Indonesia: Differences of Teaching and Learning Methods (Theory-Based) Used by Engineering TVET Teachers - Md Yunos, Jailani; Ganefri; Alias, Maizam; Ibrahim Mukhtar, Marina; Ming Foong, Lee; Tze Kiong, Tee; Rubani, Siti Nur Kamariah; Yunus, Faizal Amin Nur; Sulaiman, Junita; Sumarwati, Sri (Journal of Technical Education and Training, 2020)
This study was conducted to generate empirical evidence of the differences of teaching and learning methods used by engineering TVET teachers of Malaysia and Indonesia. This study applied quantitative method that involved data collection through the newly developed instrument of teaching and learning strategies. A survey technique was used as the research design in which a total of 183 teachers from Malaysia-Indonesia vocational institutions were involved in this research. The results have shown that there were similarities and differences of the method used by the teachers. There are several teaching and learning methods used by Malaysian and Indonesian respectively. Meanwhile, there is one similar method used by both countries which is practicing. In conclusion, Vocational Pedagogy plays a crucial role in this context, and this is why the teaching and learning is very important in educating young Malaysian and Indonesian to become successful technical and vocational trainers, instructors and teachers.